2017
DOI: 10.1089/dia.2017.0150
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Safety and Functionality of an Artificial Pancreas System for Use in Younger Children: Input from Parents and Physicians

Abstract: Parents and physicians were eager for AP applications to be available for younger children, but stressed that a modified system could better serve this group's needs for safety and improved diabetes-related communication. The diverse and emerging needs of 5-8-year olds require flexible and customizable systems for T1D management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…This stresses the importance of studying product characteristics in AP system acceptance research identified in previous literature. 6,10,13,15,16,18,19 Moreover, it contributes to this literature by providing insight into two additional factors: technology readiness and social influence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This stresses the importance of studying product characteristics in AP system acceptance research identified in previous literature. 6,10,13,15,16,18,19 Moreover, it contributes to this literature by providing insight into two additional factors: technology readiness and social influence.…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12] Previous research into psychosocial factors has given relevant insights into the overall likelihood of AP systems' future acceptance. 10,[13][14][15][16][17] In addition, it has identified two potential determinants of AP acceptance: product characteristics (ie, ease of use and usefulness) 6,10,13,15,16,18,19 and treatment satisfaction. 10,13 Bevier et al 10 have statistically examined the relationship between AP system acceptance and its determinants.…”
mentioning
confidence: 99%
“…Families have grown accustomed to remote monitoring of CGM data; many will seek closed-loop insulin delivery systems that afford this option (32). Parents of infants and toddlers value insulin pump systems that have incorporated remote bolusing features, and similar functions should be incorporated in HCL systems.…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 99%
“…Parents of infants and toddlers value insulin pump systems that have incorporated remote bolusing features, and similar functions should be incorporated in HCL systems. While limited access to various system features may be desired for youngsters, as children mature and display greater understanding of their own condition, the use of passcodes or variable access categories may allow the system to "grow" with them (32). Other focus groups have expressed the desire for these devices to be more discreet (33).…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 99%
“…To improve usability and acceptability, studies have elicited a user perspective. [1][2][3] Many have consulted individuals who have no direct experience of using the technology 1,[3][4][5][6] and have found that, as well as having high expectations, people question whether they will be able to trust the system. [3][4][5] This has prompted concerns that people's attitudes and expectations may present barriers to using the technology.…”
Section: Introductionmentioning
confidence: 99%